2004
DOI: 10.1073/pnas.0305888101
|View full text |Cite
|
Sign up to set email alerts
|

Cells have distinct mechanisms to maintain protection against different reactive oxygen species: Oxidative-stress-response genes

Abstract: The complete set of viable deletion strains in Saccharomyces cerevisiae was screened for sensitivity of mutants to five oxidants to identify cell functions involved in resistance to oxidative stress. This screen identified a unique set of mainly constitutive functions providing the first line of defense against a particular oxidant; these functions are very dependent on the nature of the oxidant. Most of these functions are distinct from those involved in repair and recovery from damage, which are generally in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
359
1
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(398 citation statements)
references
References 47 publications
31
359
1
7
Order By: Relevance
“…1B-D). These results are consistent with the notion that different genes are required to protect cells against different stresses [21].…”
Section: Tmem85v2 Protects Against Reactive Oxygen Speciessupporting
confidence: 92%
See 1 more Smart Citation
“…1B-D). These results are consistent with the notion that different genes are required to protect cells against different stresses [21].…”
Section: Tmem85v2 Protects Against Reactive Oxygen Speciessupporting
confidence: 92%
“…3B). The analysis of the complete set of viable gene deletion strains from yeast has lead to the identification of several hundred genes that are re- quired for complete resistance to oxidative stresses including H 2 O 2 [21]. Our results are consistent with this study since YGL231c was not identified in the screen.…”
Section: Yeast Tmem85 Protects Against H 2 O 2 Induced Stresssupporting
confidence: 89%
“…Among these genes, deletion of CCS1 showed the highest sensitivity to both diamide and menadione. This is inline with a previous study which also showed that sod1D cells were sensitive to both menadione and diamide [22]. …”
Section: Oxidative Stress Tolerancesupporting
confidence: 92%
“…It has been demonstrated that the deletion of single genes in the ergosterol synthesis pathway rendered yeast cells more susceptible to oxidative stress (Branco et al 2004; Thorpe et al 2004). In addition, H2O2 was found to repress the ergosterol biosynthesis pathway through Pof14, a new member of the Fbox protein family, which binds and decreases the activity of the squalene synthase ERG9, a key enzyme in ergosterol metabolism, leading to a decrease of the total cellular ergosterol levels in Schizosaccharomyces pombe (Tafforeau et al 2006).…”
Section: Discussionmentioning
confidence: 99%